HUBUNGAN ANTARA PENGETAHUAN, SIKAP, DAN KETERSEDIAAN FASILITAS DI SEKOLAH DALAM PENERAPAN PHBS MEMBUANG SAMPAH PADA TEMPATNYA (Studi di Sekolah Dasar Negeri Banjarsari 02 Kecamatan Gabus Kabupaten Pati ) - Raharjo, Ahmat Sigit; Indarjo S.KM., M.Kes, Sofwan (Unnes Journal of Public Health, 2014)
The problems are examined in this research derived from the preliminary observations which showed that the application of PHBS in Public Elementary School Banjarsari 02 sub-district Gabus district Pati do not meet the requirements as stipulated in the national policy promoting the health to support efforts to improve the healthy behavior based on minister of health No. 2269 / MENKES / PER / XI / 2011 “guidelines for guidance about clean and healthy living behavior (PHBS)”. The aim of this research is to find out the relationship between knowledge, attitude, and the availability of facilities in school by the application of PHBS disposing of garbage on exactly.A kind of this research explanatory research with the approach of cross-sectional. Population in this research is of public elementary school students Banjarsari 02 sub-district Gabus district Pati 2012. Samples were 46 students. An instrument used namely a questionnaire. Analysis of data done in univariat and bivariat ( fisher ).The results of this research is relationship between knowledge ( p = 0,037), attitude (p = 0,007), the availability of facilities in school ( p = 0,002 ) by the application of PHBS disposing of garbage in place. The advice given to public elementary school Banjarsari 02 sub-district Gabus district Pati, should be given counseling about PHBS. Provides a facility that are amenable to the students to want to apply PHBS disposing of garbage in place. For health department, the county of Pati program should monitor PHBS particularly in the order school.